Pengembangan Teknologi ERP Untuk Modul Human Resource Management Studi Kasus PT. Imperium Happy Puppy Sampit - Muhaimin Muhaimin; Lukman Bachtiar (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
PT. Imperium Happy Puppy is a company engaged in karaoke entertainment, the first to adopt the concept of family karaoke, where this company has many branches spread throughout Indonesia, one of which is in the area of ​​Sampit, Central Kalimantan. However, in this company there are problems in managing employees, namely: recruitment, managing employee bio data, scheduling, managing attendance, filing for leave, promotions, assessments, payroll which are still not fully computerized in this case still using Ms. Office to manage these data. So that it is very difficult for HRD leaders to see the report data concerning employees. Therefore, ERP (Enterprise Resources Planning) technology can be the right tool to solve these problems. One of them is by using the HRM (Human Resources Management) module, with the hope of producing fast and precise information and helping companies make decisions.